Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.3 - Multiplying and Factoring Algebraic Expressions - Exercises - Page 21: 42


y=$-\frac{3}{2}$ or $x=-\frac{4}{3}$

Work Step by Step

$6y^{2}+17y+12$ =$6y{2}+8y+9y+12$ =$2y(3y+4)+3(3y+4)$ $(2y+3)(3y+4)$$=0$ y=$-\frac{3}{2}$ or $x=-\frac{4}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.